Green processing of metal oxide core-shell nanoparticles as low-temperature dielectrics in organic thin-film transistors - Portilla, Luis (Advanced materials (Deerfield Beach, Fla.), 2015)
© 2015 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.